How Large are Predefault Costs of Financial Distress? Estimates from a Dynamic Model - Elkamhi, Redouane; Kim, Daniel; Salerno, Marco (Management Science, 2024)
We estimate the costs of financial distress prior to default (predefault costs) separately from the loss incurred at default (the loss given default) using a dynamic tradeoff model of capital structure. We show that predefault costs account for a large fraction of total distress costs, approximately 64.1%. At the same time, they vary across industries ranging from 32.1% to 75%. We demonstrate that the expected predefault costs of financial distress vary significantly across industries with a range between 3.2% and 8.3% and are higher for small firms relative to larger ones. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.4974 .